Asymptomatic HIV positive patient presenting with myelopathy - Jatin Agrawal (International Journal of Advanced Medical and Health Research, 2016)
A wide variety of disorders of diverse pathogenic mechanisms can trigger spinal cord dysfunction in HIV-1-infected patients. The most common such condition is HIV-1-associated myelopathy (HAM) which characteristically seen during advanced HIV infection in patients with low CD4 cell counts and previous AIDS-defining diagnoses. Histologically seen in approximately 30% of AIDS patients, but only 10% have clinical symptoms related to the disease. We describe an unusual case of HAM in previously asymptomatic patient with relatively low CD4 cell count (78 cells/mm3). The patient unaware of her seropositive status presented with a clinically slowly progressive myelopathy with difficulty in walking without assistance. We discharged a patient on antiretroviral therapy. We also review the disorders reported to derange spinal cord function in previously asymptomatic HIV-1 infected patients with preserved counts.